Factors Associated with Unintentional Injury among University Students in 26 Countries. Issue 5 (3rd February 2015) - Peltzer, Karl; Pengpid, Supa
Abstract Objective The aim of this study was to determine estimates of the incidence and social correlates of nonfatal injury among university students in 26 low‐, middle‐, and high‐income countries. Design and Sample Using anonymous questionnaires, data were collected in a cross‐sectional survey of 19, 111 undergraduate university students (mean age 20.8, SD = 2.8) from 27 universities in 26 countries across Asia, Africa, and the Americas. Measures Questionnaire on health risk behaviors, psychological distress, personality, social variables, and injury requiring medical treatment or missing at least one day of usual activities. Results The percentage of university students reporting one or more serious injuries within the past 12 months was 25.2% for all countries, in men 28.8% and women 21.1%. In multivariate logistic regression among men, socio‐demographic variables, health risk behaviors, posttraumatic stress (PTSD) symptoms, lack of personal control and lack of social support, and among women, residing on campus, health risk behaviors, PTSD symptoms, lack of personal control, and lack of social support were associated with injury incidence. Conclusions Several risk factors were identified which will increase the understanding of public health nurses of injuries in university communities to design programs for injury prevention programs specifically targeting university students, staff, and university health center professionals.